CRISPR/Cas9‐mediated functional recovery of the recessive rc allele to develop red rice. Issue 11 (7th May 2019) - Zhu, Yiwang; Lin, Yarong; Chen, Songbiao; Liu, Huaqing; Chen, Zaijie; Fan, Meiying; Hu, Taijiao; Mei, Fating; Chen, Jianmin; Chen, Liang; Wang, Feng
Summary: Red rice contains high levels of proanthocyanidins and anthocyanins, which have been recognized as health‐promoting nutrients. The red coloration of rice grains is controlled by two complementary genes, Rc and Rd . The RcRd genotype produces red pericarp in wild species Oryza rufipogon, whereas most cultivated rice varieties produce white grains resulted from a 14‐bp frame‐shift deletion in the seventh exon of the Rc gene. In the present study, we developed a CRISPR/Cas9‐mediated method to functionally restore the recessive rc allele through reverting the 14‐bp frame‐shift deletion to in‐frame mutations in which the deletions were in multiples of three bases, and successfully converted three elite white pericarp rice varieties into red ones. Rice seeds from T1 in‐frame Rc lines were measured for proanthocyanidins and anthocyanidins, and high accumulation levels of proanthocyanidins and anthocyanidins were observed in red grains from the mutants. Moreover, there was no significant difference between wild‐type and in‐frame Rc mutants in major agronomic traits, indicating that restoration of Rc function had no negative effect on important agronomic traits in rice. Given that most white pericarp rice varieties are resulted from the 14‐bp deletion in Rc, it is conceivable that our method could be applied to most white pericarp rice varieties and would greatly accelerate the breeding of new red rice varieties with elite agronomic traits. In addition, our study demonstrates an effective approach to restore recessive frame‐shift alleles for crop improvement.